The prevalence of odontogenic maxillary osteitis at the Cocody University Hospital's Odontostomatological Consultation and Treatment Center (CCTOS), Abidjan (Ivory Coast): clinical and therapeutic aspects - Kouamé Patrice A.; Ayé Marcellin; Amantchi Daniel; Kouyaté Vazoumana; Atsé Sylvie Koboh N'guessan; Zié Traoré; Saint Honoré Oheueu S.; Adouko Jeannette A. (EDP Sciences, 2021)
Maxillary osteitis is a bone tissue disease or condition with a dentoalveolar origin. This condition remains a public health concern in most developing countries, particularly in the Ivory Coast. Without appropriate management, it can alter the patient's overall health owing to aesthetic, functional, and psychological complications. This study aimed to provide a better understanding of odontogenic maxillary osteitis to consequently improve its diagnosis and medical care. Three major etiologies of maxillary osteitis have been reported: infectious, traumatic, and physicochemical causes. According to the literature, osteitis is grouped into two clinical forms, namely circumscribed osteitis and diffuse osteitis. Their diagnosis is based on a rigorous clinical examination as well as radiographic, histological, and bacteriological examinations. At the Cocody University Hospital's Odontostomatological Consultation and Treatment Center (CCTOS), patients with the late stages of the condition present with significant, disabling, and unsightly osteocutaneous-mucous lesions. Treatment of this osteitis is preventive, curative, and restorative. Odontogenic maxillary osteitis is encountered frequently and typically at a late stage at the Cocody University Hospital's CCTOS. To limit aesthetic and functional damage, raising awareness among African people about oral hygiene and the need for regular consultations should be encouraged.